PENGARUH PENAMBAHAN PENDINGIN AIR PADA TRANSFORMATOR DAYA UNTUK PEMBEBANAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Power transformers are one of the important equipment in the electric power system. Power transformers are devices with the largest investment in a transmission and distribution substations. Currently, the use of power transformers at Marunda substations on average has reached 80% of rated load. Then require maximum of cooling transformers, to restrain the rate of the winding and oil temperature rise. Result of the research were obtained with the addition of water cooling at power transformers can be reduce the heat due to the high ambient temperatures. The results showed a decrease in temperature of 3°C, so can be used to add transformers loading of 2,51 MW. While of water consumption was 2,052 m3 per day.